DPP-4 Inhibitor Linagliptin Ameliorates Oxidized LDL-Induced THP-1 Macrophage Foam Cell Formation and Inflammation - Wang H (Drug Design, Development and Therapy, 2020)
Haoran Wang,1 Yue Li,2 Xiaoliang Zhang,2 Zhonglin Xu,2 Jianzhong Zhou,3 Wei Shang2 1Department of Endocrinology, The Ninth People’s Hospital of Chongqing, Chongqing 400700, People’s Republic of China; 2Department of Cardiology, The Ninth People’s Hospital of Chongqing, Chongqing 400700, People’s Republic of China; 3Department of Cardiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400700, People’s Republic of ChinaCorrespondence: Wei ShangDepartment of Cardiology, The Ninth People’s Hospital of Chongqing, No. 69, Jia Ling Road, Bei Bei District, Chongqing 400700, People’s Republic of ChinaTel +86-15823409229Email wshang355@163.comIntroduction: Atherosclerosis is one of the major causes of cardiovascular diseases. Lipid uptake and accumulation in macrophages play a major role in atherosclerotic plaque formation from its initiation to advanced atheroma formation. The dipeptidyl peptidase-4 (DPP-4) inhibitor Linagliptin is commonly used to lower blood glucose in type 2 diabetes patients. Recent studies report that Linagliptin has cardiovascular protective and anti-inflammatory effects.Methods: THP-1 macrophage cells were treated with 100 nM PMA for 72 hour to induce foam cell formation. The differentiated cells were exposed to 100 μg/mL ox-LDL in the presence or absence of the DPP-4 inhibitor Linagliptin. The expression levels of DPP-4 and inflammatory cytokines were detected by RT-PCR, ELISA, and Western blot experiments. The cellular ROS level was measured by staining the cells with the fluorescent probe DCFH-DA. The separation of lipoprotein fractions was achieved by high-performance liquid chromatography (HPLC). The cells were labeled with fluorescent-labeled cholesterol to measure cholesterol efflux, and lipid droplets were revealed by Nile red staining.Results: The presence of Linagliptin significantly reduced ox-LDL-induced cytokine production (IL-1β and IL-6) and ROS production. Linagliptin ameliorated ox-LDL-induced lipid accumulation and impaired cholesterol efflux in macrophages. Mechanistically, this study showed that Linagliptin mitigated ox-LDL-induced expression of the scavenger receptors CD36 and LOX-1, but not SRA. Furthermore, Linagliptin increased the expression of the cholesterol transporter ABCG1, but not ABCA1.Conclusion: Linagliptin possesses a potent inhibitory effect on THP-1 macrophage-derived foam cell formation in response to ox-LDL. This effect could be mediated through a decrease in the expression of CD36 and LOX-1 on macrophages and an increase in the expression of the cholesterol transporter ABCG1. This study indicates that the DPP-4 inhibitor Linagliptin plays a critical role in preventing foam cell formation in vitro. However, future research using an atherosclerotic animal model is necessary to determine its effectiveness and to prove its potential implication in the prevention and treatment of atherosclerosis.Keywords: atherosclerosis, foam cells, Linagliptin, CD36, LOX-1, ABCG-1, ATP binding cassette transporter G1